2018
DOI: 10.3390/catal8070279
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active TiO2 Microspheres Formation in the Presence of Ethylammonium Nitrate Ionic Liquid

Abstract: Spherical microparticles of TiO 2 were synthesized by the ionic liquid-assisted solvothermal method at different reaction times (3, 6, 12, and 24 h). The properties of the prepared photocatalysts were investigated by means of UV-VIS diffuse-reflectance spectroscopy (DRS), Brunauer-Emmett-Teller (BET) surface area measurements, scanning electron microscopy (SEM), X-ray diffraction analysis (XRD), and X-ray photoelectron spectroscopy (XPS). The results indicated that the efficiency of the phenol degradation was … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…This explication is in a strong agreement with several research studies, which reported that IL-modified metal oxides could exhibit better photocatalytic activity than the bare metal oxides since they have less energy bandgaps. [37,43,50,51] Additionally, the increase of [OMIM]Br content in the photocatalyst to represent half its molar composition is another reason behind its elevated hydrogen productivity. Specifically, this increment could further inhibit the recombination of charge carriers during the excitation state of the photocatalyst.…”
Section: Photocatalytic Activity Of [Omim]br/fecl 3 Ilsmentioning
confidence: 99%
“…This explication is in a strong agreement with several research studies, which reported that IL-modified metal oxides could exhibit better photocatalytic activity than the bare metal oxides since they have less energy bandgaps. [37,43,50,51] Additionally, the increase of [OMIM]Br content in the photocatalyst to represent half its molar composition is another reason behind its elevated hydrogen productivity. Specifically, this increment could further inhibit the recombination of charge carriers during the excitation state of the photocatalyst.…”
Section: Photocatalytic Activity Of [Omim]br/fecl 3 Ilsmentioning
confidence: 99%
“…On the basis of our previous research on the preparation of TiO 2 microspheres via the ionic liquid assisted solvothermal method, [EAN]­[NO 3 ] was chosen as a structural agent promoting preparation of photocatalyst with an extremely high photocatalytic activity under visible irradiation . Therefore, in this study, we aimed to assess the effect of this IL on the structure, surface, and photocatalytic activity of TiO 2 NTs prepared in the electrochemical way.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a controllable preparation of the functional TiO2 semiconductor employing ionic liquids is a new and effective approach [10,11]. Nevertheless, the mechanism of IL action and their role in the TiO2 photoactivity enhancement have not been fully explained yet.…”
Section: Resultsmentioning
confidence: 99%